Peran Reliugisitas pada Penderita HIV dan AIDS yang mengalami Depresi - Prasojo, Dibyo (Jurnal Studia Insania, 2017)
Being HIV-positive (people with HIV and AIDS) is a tough one in life, where complex problems are always faced daily, not just dealing with disease conditions, but disease conditions are accompanied by highly discriminatory social stigma. This stigma and discrimination often leads to depression resulting in a decrease in life spirits of people living with HIV and then bring the dominant effect of decreasing quality of life for people living with HIV. This study aims to reveal the role of religiosity in coping with depression in people with HIV and AIDS in terms of physical, psychological, social, and religiosity and factors that support the role of religiosity in coping with depression in people with HIV and AIDS. The research approach used is qualitative in the form of case studies. Subjects studied in the study are ODHA are running post-positive religiosity of HIV and AIDS consisting of 1 man and 2 women. Data collection techniques used are unstructured interviews and nonparticipant observation. While the research data collection tool used interview, observation, recorder and stationery. And the result of research data will be analyzed by using qualitative analysis technique. Based on the results of research that has been done can be stated that the role of religiosity in tackling Depression in HIV and AIDS Patients in RSUD Dr. H. Moch. Ansyari Saleh Banjarmasin is very large, seen from all subjects feel the change of attitude and view to get closer to God. Appreciate life in its true sense, enjoy life and resign to accepting circumstances. Factors that support the role of religiosity in people with HIV and AIDS in RSUD Dr. H. Moch. Ansyari Saleh Banjarmasin there are two namely: first internal factors, which are related to innate nature, and the second is external factors derived from the environment such as family and society.Â